TUBERCULOSE: UM ESTUDO DE CASO - Grimm, Júlia Y.; Freire, Maria R. A.; Morais, Cheila L. O.; Weiss, Elisângela d. C.; Santoni, Michele; Kolankiewicz, Adriane C. B. (Salão do Conhecimento, 2013)
Resumo